Child Welfare Caseworkers and Children with Developmental Disabilities: An Exploratory Study. Issue 2 (31st January 2019) - Rao, Trupti; Reiman, Elizabeth; Ausikaitis, Ashley
Abstract: Children with developmental disabilities are overrepresented in the child welfare system. Although caseworkers play a key role in ensuring that the special needs of these children are met, little is known regarding caseworkers' knowledge about, exposure to, and comfort with people with developmental disabilities. In this exploratory study, through use of an online anonymous survey, local county caseworkers ( N = 251) were asked to self-rate their knowledge, exposure, and comfort levels. Findings indicated caseworker agreement regarding the relevance of having knowledge and training about this population within the child welfare system. Furthermore, caseworkers with more training felt more knowledgeable and comfortable than those with less training. In addition, personal exposure to individuals with developmental disabilities was considered relevant.